Impaired cerebral glucose metabolism in prodromal Alzheimer's disease differs by regional intensity normalization - Küntzelmann, Anika; Guenther, Thomas; Haberkorn, Uwe; Essig, Marco; Giesel, Frederik L.; Henze, Romy; Schroeter, Matthias L.; Schröder, Johannes; Schönknecht, Peter (Neuroscience letters, 2013)
Using [18F] fluorodeoxyglucose (FDG) positron emission tomography (PET) patients with Alzheimer's disease show impairment of cerebral glucose metabolism in bilateral frontotemporoparietal association cortices and posterior cingulate cortex whereas in patients with mild cognitive impairment (MCI) results are heterogeneous. For the first time, the present study examined alterations of the cerebral glucose metabolism in patients with prodromal AD as compared to patients with AD dementia and healthy controls depending on intensity normalization. 15 patients with AD (69.8±8.5 years) and 28 with prodromal AD (67.4±9.1 years) as well as 10 healthy controls (58.8±5.9 years) underwent FDG PET under resting conditions. By statistical parametric mapping 8, analyses were performed using (a) cerebellar cortex or (b) whole brain as reference region for intensity normalization. Patients with AD dementia showed reductions in bilateral temporoparietal regions and posterior cingulate gyrus as compared to controls. By contrast, patients with prodromal AD had only reductions in the left posterior temporal lobe and left angular gyrus as compared with controls. Cerebellar normalization was superior in differentiating patients with prodromal AD or AD dementia from healthy controls, but global normalization provided slightly better contrasts for the differentiation between patients with prodromal AD and AD dementia in AD-typical regions. Unexpected hypermetabolism in patients was only revealed using global normalization and has to be regarded as an artifact of intensity normalization to a reference region affected by the disease.
Available online 23 November 2012
Gesehen am 28.06.2021